2022
DOI: 10.1007/s11227-022-04970-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal prediction of cloud spot instance price utilizing deep learning

Abstract: Cloud platforms frequently provide a variety of virtual machine models (VMs) with varying types and capacities, allowing users to select instances that best suit their needs. Cloud providers have devised a system for maximizing the utilization of redundant computing resources, whose costs fluctuate dynamically depending on supply and demand. "Spot pricing" is a common term for this, the user must make a suitable offer that is higher than the spot price to use this instance. Accurate spot price prediction enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Spot instance price prediction was carried out using k-nearest neighbors (KNN) in [11]. In [12,13], the authors adopted several machine-learning approaches to forecast the future pricing of EC2 spot instances, such as linear, ridge, and lasso regressions, multilayer perceptrons, k-nearest neighbors, extra trees, and random forests. Based on the results, machine learning is an encouraging approach for predicting spot prices.…”
Section: Ml-driven Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Spot instance price prediction was carried out using k-nearest neighbors (KNN) in [11]. In [12,13], the authors adopted several machine-learning approaches to forecast the future pricing of EC2 spot instances, such as linear, ridge, and lasso regressions, multilayer perceptrons, k-nearest neighbors, extra trees, and random forests. Based on the results, machine learning is an encouraging approach for predicting spot prices.…”
Section: Ml-driven Approachmentioning
confidence: 99%
“…In order to provide a comprehensive comparison, several studies have examined spot instance pricing and reported MAPE values. These studies [11][12][13] have found that shortterm forecasts, typically ranging from 1 to 3 hours ahead, exhibit MAPE values between 10% and 20%. Conversely, longer-term forecasts, specifically those made 24 h in advance, demonstrate MAPE values ranging from 20% to 40%.…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In [40], the authors proposed a modified gated recurrent unit (MGRU) model and compared its performance to five other statistical and deep learning methods:…”
Section: Almentioning
confidence: 99%